METTL14 Mediates Glut3 m6A methylation to improve osteogenesis under oxidative stress condition - Ying Wang; Xueying Yu; Fenyong Sun; Yan Fu; Tingting Hu; Qiqing Shi; Qiuhong Man (Redox Report)
Objectives Bone remodeling imbalance contributes to osteoporosis. Though current medications enhance osteoblast involvement in bone formation, the underlying pathways remain unclear. This study was aimed to explore the pathways involved in bone formation by osteoblasts, we investigate the protective role of glycolysis and N6-methyladenosine methylation (m6A) against oxidative stress-induced impairment of osteogenesis in MC3T3-E1 cells.Methods We utilized a concentration of 200 μM hydrogen peroxide (H2O2) to establish an oxidative damage model of MC3T3-E1 cells. Subsequently, we examined the alterations in the m6A methyltransferases (METTL3, METTL14), glucose transporter proteins (GLUT1, GLUT3) and validated m6A methyltransferase overexpression in vitro and in an osteoporosis model. The osteoblast differentiation and osteogenesis-related molecules and serum bone resorption markers were measured by biochemical analysis, Alizarin Red S staining, Western blot and ELISA.Results H2O2 treatment inhibited glycolysis and osteoblast differentiation in MC3T3-E1 cells. However, when METTL14 was overexpressed, these changes induced by H2O2 could be mitigated. Our findings indicate that METTL14 promotes GLUT3 expression via YTHDF1, leading to the modulation of various parameters in the H2O2-induced model. Similar positive effects of METTL14 on osteogenesis were observed in an ovariectomized mouse osteoporosis model.Discussion METTL14 could serve as a potential therapeutic approach for enhancing osteoporosis treatment.